Cystatin C in healthy middle-aged adults: A relationship with anthropometric and cardiometabolic parameters (Journal of Health Sciences, 2016)
Introduction: Data suggesting that cystatin C levels are linked to obesity, apart from renal pathology, are conflicting. The aim of the study was to explore the potential association between serum cystatin C levels, anthropometric, and cardiometabolic parameters in healthy middle-aged adults.Methods: A total of 132 participants (mean age 56.2 ± 6.73 years, 69% females) were included in this cross-sectional study. Anthropometric and biochemical parameters, as well as blood pressure, were obtained.Results: Obese participants displayed higher cystatin C levels than normal-weight participants (p < 0.001). Multiple linear regression analysis revealed that waist circumference (WC) (Beta = 0.376, p < 0.001) and estimated glomerular filtration rate (Beta = -0.484, p < 0.001) were independently associated with cystatin C levels (R2 = 0.447; p < 0.001).Conclusions: Cystatin C is associated with abdominal obesity independent of renal function. Its relationship with changes in other target organs should be determined.